ENTREPRENEURIAL TRAITS AND FIRM PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN PORT HARCOURT, NIGERIA (American Journal of Interdisciplinary Research and Development, 2025)
Abstract This study examined the relationship between entrepreneurial traits and firm performance among Small and Medium Enterprises (SMEs) in Port Harcourt, Nigeria. Specifically, the study investigated the influence of innovativeness and risk-taking propensity on financial performance indicators such as profitability, sales growth, and market share. Grounded in Trait Theory of Entrepreneurship and the Resource-Based View, the research adopted a quantitative correlational design. A census approach was used to collect data from 96 owners and managers across 30 selected SMEs within Port Harcourt Metropolis, with 91 valid responses analyzed using descriptive statistics and Pearson Product Moment Correlation at a 0.05 significance level. The findings revealed a strong positive and statistically significant relationship between innovativeness and financial performance (r = 0.859, p < 0.01), as well as between risk-taking propensity and financial performance (r = 0.741, p < 0.01). The results indicate that SMEs led by entrepreneurs who actively support innovation and engage in calculated risk-taking tend to achieve superior financial outcomes. The study concludes that entrepreneurial traits function as strategic internal resources that enhance SME competitiveness and sustainability in resource-constrained and volatile environments. The research contributes context-specific empirical evidence from Port Harcourt and offers practical implications for policy and entrepreneurial capacity development in emerging economies.